Quality control of phytopharmaceuticals with the use of Nuclear Magnetic Resonance (NMR) and the application of principal component analysis (PCA) - Quesada-Espinoza, Javier (2019)
The phytopharmaceuticals, although they are generally composed of natural products, must be strictly controlled regarding their content of active ingredients. There are several methods of quality control among which stand out liquid chromatography and mass spectrometry; in our research, we carried out a quality control with the use of Nuclear Magnetic Resonance, which is easy to use and interpret, and highly versatile, as well as non-destructive technique, and with this information a study of principal components was carried out in order to obtain a better visualization of the results. In this work we demonstrated that in Costa Rica there is a large number of products marketed that apparently do not contain the active ingredients that should have according to the labeling, as could be demonstrated in the case of the products of Gingko biloba, Hypericum perforatum and Silybum marianum. In the case of Equinacea spp, the problem of the comparison was that the different products contain several species of the same genus and this makes a detailed analysis difficult. In addition, the analysis of main components made it possible to demonstrate that it is difficult to use this technique without prior knowledge of the analysis techniques used, and what must to be interpreted. The results also indicate that regulations in Costa Rica are not rigorous enough for this type of products, and these should be reviewed by the National Regulatory Agency.